2012
DOI: 10.1158/1078-0432.ccr-10-3186
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltration by T Lymphocytes Expressing Chemokine Receptor 7 (CCR7) Is Predictive of Favorable Outcome in Patients with Advanced Colorectal Carcinoma

Abstract: Purpose: An efficient adaptive immunity is critical for a longer survival in cancer. We investigated the prognostic value of tumor infiltration by CD8 þ T cells expressing the chemokine-receptor-7 (T ccr7 ) and the correlation between tumor infiltration by T ccr7 and regulatory CD4 Conclusions: High T ccr7 tumor infiltration score is a favorable prognostic factor for mCRC. Our findings underline the relevance of microenvironment-related immunologic events for patient outcome. Clin Cancer Res; 18(3); 850-7. Ó20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 38 publications
8
69
0
Order By: Relevance
“…50 Thus, an increased number of CCR7 C T-cells in the tumor sites indicates a greater amount of freshly mobilized resource of immune-effectors. In a previous study, we already showed that a greater infiltration by CD8 C CCR7 C T-cells in the primary tumors is predictive of better outcome in metastatic colorectal carcinoma patients 27,28 and similar results were also achieved by others in different malignancies. [51][52][53][54] Conversely, T reg s (…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…50 Thus, an increased number of CCR7 C T-cells in the tumor sites indicates a greater amount of freshly mobilized resource of immune-effectors. In a previous study, we already showed that a greater infiltration by CD8 C CCR7 C T-cells in the primary tumors is predictive of better outcome in metastatic colorectal carcinoma patients 27,28 and similar results were also achieved by others in different malignancies. [51][52][53][54] Conversely, T reg s (…”
Section: Discussionsupporting
confidence: 84%
“…[16][17][18][19][20][21][22][23][24][25] In particular, the results of previous studies by our group showed that primary tumor infiltration by immune-regulatory T cells (CD25 , namely T cm ) are associated to a prolonged PFS and OS in patients with metastatic colorectal carcinoma undergone frontline chemotherapy. [26][27][28] On these bases, we investigated whether infiltration of the primary tumor by different lymphocyte subsets may predict the outcome of PC patients. In order to avoid possible interferences and biases related to frequent cancer co-morbidities, multiple medications, aging, and massive bone marrow infiltration associated with metastatic prostate cancer, we focused our retrospective study to a well-defined PC patient population, already treated with radical prostatectomy, with a good performance status, who received RT upon BR.…”
Section: Introductionmentioning
confidence: 99%
“…Based on some experimental findings, it appears that an immune modulating effect should be considered even for mAbs used in aGC treatment. [80][81][82][83][84][85][86] Interestingly, in aGC, while bevacizumab did not demonstrate a significant benefit, indeed, in our analysis, we observed that trials evaluating other agents showed a highly significant efficacy in term of survival benefit in the anti-angiogenesis subgroup in aGC. 17,35,37 Several studies suggested that targeting VEGFR2 may elicit and improve the immune response directed toward the tumor and its microenvironment trough different mechanisms including direct activation of CD8 C cells and targeting of the FOXP3 high regulatory T cells.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, previous results by our group suggested that basal tumor infiltration by both T CCR7 and T reg lymphocyte is predictive of favorable outcome in metastatic CRC patients and that chemo-immunotherapy may modulate patients' own immune-response. [36][37][38][39] We believe that these findings underline the central role of the interplay between inflammation, angiogenesis and immune system in conditioning cancer patients' survival and response to treatment supporting the potential role of chemo-immunotherapy in NSCLC. 40,41 Our study presents some limitations such as the low number of enrolled patients especially in the control/calibration group, the lack of a validation data set in an independent patient cohort contributing to the preliminary character of this report.…”
Section: Methodsmentioning
confidence: 58%